2017
DOI: 10.1007/s10461-017-2013-1
|View full text |Cite
|
Sign up to set email alerts
|

Improving AIDS Care After Trauma (ImpACT): Pilot Outcomes of a Coping intervention Among HIV-Infected Women with Sexual Trauma in South Africa

Abstract: ClinicalTrials.gov NCT02223390.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(102 citation statements)
references
References 62 publications
4
94
0
Order By: Relevance
“…While previous studies have described how avoidant approaches to dealing with life stressors can lead to drinking and depression among PLWH [32,38], far less attention has been given to the role of traumatic life experiences and social circumstances. Although there have been some efforts to develop interventions that address traumatic stress among South African women who are living with HIV [39,40], these interventions have not included a focus on alcohol use and depression which intersect with experiences of trauma; other trauma-focused substance use interventions have been developed but have not focused on young women using ART specifically [35,41]. Our findings suggest that helping young women living with HIV to find ways of accepting problems and life circumstances that cannot change, including strategies for helping women manage their emotional responses to these experiences, is key to enabling them to move on with their lives, change their health risk behaviors, and optimize their use of ART.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have described how avoidant approaches to dealing with life stressors can lead to drinking and depression among PLWH [32,38], far less attention has been given to the role of traumatic life experiences and social circumstances. Although there have been some efforts to develop interventions that address traumatic stress among South African women who are living with HIV [39,40], these interventions have not included a focus on alcohol use and depression which intersect with experiences of trauma; other trauma-focused substance use interventions have been developed but have not focused on young women using ART specifically [35,41]. Our findings suggest that helping young women living with HIV to find ways of accepting problems and life circumstances that cannot change, including strategies for helping women manage their emotional responses to these experiences, is key to enabling them to move on with their lives, change their health risk behaviors, and optimize their use of ART.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of potentially promising interventions have not shown gains for ART initiation. No benefit was seen in a South African study involving a conditional economic incentive (39% intervention versus 45% control; adjusted odds ratio (AOR) = 0.67; 95% CI = 0.26-1.78) [30] or in a Kenyan study involving weekly text message (WelTel Retain; 82% versus control 78%) [31], or a sexual trauma coping intervention for women with a history of sexual abuse in South Africa (91% intervention versus 88% SoC) [32].…”
Section: General Adult Populationsmentioning
confidence: 99%
“…Interpersonal violence and sexual trauma are highly prevalent among this population [5,6]. Our group has previously shown that nearly two-thirds of WLHIV have experienced sexual trauma and that many do not disclose this history unless asked under research or strict clinical conditions [7,8]. The consequences of these experience(s) include increased rates of depression and post-traumatic stress disorder [9], and increased likelihood of behavioural avoidance patterns [6,[10][11][12]].…”
Section: Interpersonal Violence and Sexual Traumamentioning
confidence: 99%
“…WLHIV with a history of sexual trauma already live with high levels of anxiety, including hyper-arousal and avoidance symptoms [8]. They cope poorly with additional stressors [11,15].…”
Section: Interpersonal Violence and Sexual Traumamentioning
confidence: 99%
See 1 more Smart Citation